PEMANFAATAN CITRA ALOS PALSAR UNTUK ESTIMASI KANDUNGAN SERAPAN KARBON DI WILAYAH PESISIR KABUPATEN MAROS - Muh Faisal M.; Muliana Djafar; Andi Ayu Nurnawati (Program Studi Kehutanan Universitas Muslim Maros, 2021)
This study aims to determine the type of land use in 2009 using alos palsar image, then calculate carbon stocks and sequestration using the 2006 IPCC Software approach. The data sources of this research are primary data and secondary data. Primary data in the form of data obtained through the interpretation of Alos Palsar Imagery, while secondary data is data obtained from literature studies concerning the results of measurement data in the form of volume, diameter and tree height at the research location. The data will be calculated using IPCC GL 2006 software. The results showed that the land cover of the coastal area of Maros Regency based on Citra Alos was dominated by ponds and grasslands with an area of 59.05 ha of the total coastal area, while the forested area was only a small part, namely 1.16% mangrove forest and 0.94% agroforestry. Mangrove forest and agroforestry are the largest carbon storage areas in the coastal area with 96,223.52 and 33,608.81 tons, respectively. Based on IPCC mangrove forest and agroforestry have carbon sequestration of 22.39 and 9.6 tons/(ha/year, respectively). However, with carbon sequestration of only around 2.4 and 5.1 ton/(ha/year) rice fields and shrubs actually show that the total carbon absorption in coastal areas has 8,901.36 and 7,159.25 ton/year. With a very small area, mangrove forests and agroforestry are able to absorb carbon of 4,811.18 and 1680.44 tons/year.